Characteristics of summer drought circulation and the synergistic effect of multiple factors in the Northern drought-prone belt of China - Yang, Jinhu; Zhang, Qiang; Wang, Pengling; Yue, Ping; Li, Yiping; Liang, Zhuoqi; Liu, Xiaoyun (Frontiers in Environmental Science, 2024)
Drought, which is severe and recurring in Northern China, is the most significant meteorological disaster on a worldwide scale. However, a definitive conclusion has not yet been reached on the multi-scale drought features in Northern China under a warming context. Drought is affected by several circulation-related variables and a deeper scientific comprehension of their synergistic effects is required. This research addresses the spatiotemporal aspects of summer drought and its causes in the northern drought-prone belt of China (NDPB), based on meteorological observation and data reanalysis. The primary findings indicate that the NDPB is very vulnerable to drought, with the uniform mode being the region’s most significant spatial mode associated with summer droughts. Inter-annual variations are the primary cause of the summer drought in the NDPB when considering multi-scale changes. Regional drought has typically declined during this century because of the effect of multi-decadal scale changes, which cannot be disregarded. Considering the circulation background field, during summer drought years in the NDPB, the South Asian high is weaker and moves eastward, while the high-level westerly jet is weaker and more northerly. From Lake Baikal to Northern China, there is an anomalous anticyclonic circulation, and the mid-level subtropical high in the western Pacific is more southerly and easterly. As a result, the NDPB is governed by the unusual northerly circulation. The Mongolian and northeastern surface cyclone activity is decreasing, the low-level warm and humid airflow is feeble, and the NDPB is not experiencing anomalous water vapor transport. In the high-, middle-, and low-level arrangement, the NDPB circulations diverge at low levels and converge at high levels—unusual sinking in the vertical field results in regular droughts. Multiple circulation parameters on inter-annual, inter-decadal, and multi-decadal scales interact synergistically to impact summer droughts in NDPB. However, the synergistic elements that mainly impact various timescales differ. They are primarily influenced by northerly circulation, westerly winds, and the combined effect of the South Asian summer monsoon on inter-annual timescales. The combined impact of the upper westerly winds, northerly circulation, and East Asian, South Asian, and plateau summer monsoons significantly influences their inter-decadal timescales. The westerly winds, northerly circulation, and East Asian, plateau summer monsoons are the primary multi-decadal factors.